Architecting a large-scale ubiquitous e-voting solution for conducting government elections - Malladi, Kausal; Sridharan, Srivatsan; JayPrakash, L. T. (2014 International Conference on Advances in Electronics Computers and Communications, 2014)
With growing population, voting during elections for government formation has increased in scale and is a huge process across different countries of the world. At the same time, lots of possibilities exist to improve the current implementation, and in the process solutions can be given to many of its loopholes. This paper proposes a robust e-voting system using Automated Teller Machine (ATM) terminals and Micro ATMs. The proposed approach ensures duplicate vote avoidance through dual-tier authentication using One Time Password (OTP) and a Random Security Question (RSQ). To further enhance the security of such a public voting mechanism, the proposed approach assigns arbitrary Candidate IDs (CIDs) to contestants. This ensures voting privacy of a voter. However, appropriate mapping mechanism has to be used in handling arbitrary CIDs during counting of votes, which can be implemented with little effort. It should be noted that use of ATMs to provide a voting solution necessitates minor updates to the bank database schema for voter authentication and network usage. A single interface for elections at all levels enhances voter convenience to a greater extent. Use of RESTful web services ensures that load on servers is as low as possible, ensuring quick response time for all transactions. The proposed approach guarantees robustness of the e-voting system while resulting in huge dollar savings.